Modelling effective waqf administration: a solution toward accountability / Siti Sara Ibrahim … [et al.] - Ibrahim, Siti Sara; Mohd Noor, Abd Halim; Mohd Sharip, Sharfizie; Mohamad Rusli, Nurhanani Aflizan (Research Management Institute (RMI), 2016)
Waqf means holding and preservation of a certain philanthropy or sadaqah (charity) with the intention of prohibiting any use or disposition of the property outside the specific purposes to which the property is dedicated in such a way that it cannot be sold. As waqf institution covers a wide range of issue from economic to social aspect of human development, application of the professional management concepts and principles along with contemporary best practices provide the basic excellence of operation to achieve the overall efficiency and effectiveness. Therefore, this paper is intended to provide an overview on the waqf institution and to assess an effective method of waqf institution in the aspects of organization structure, legal system, financial and human resource issues. We acknowledged that there are impediments such as bureaucracy, lack of expertise and the need to revisit religious rulings on waqf in order to realize the true intent and spirit of awqaf.